Implications of TTIP and TPP on Bangladesh and Nepal - Al Amin, Mohammed Nafeez (Asian Business Review, 2015)
The Transatlantic Trade and Investment Partnership (TTIP) and the Transpacific Partnership (TPP) could the biggest trade deal in the history. The EU and the USA are in the process of, or contemplating, to sign Free Trade Agreements (FTAs) under TTIP and TPP. As, the European Union (EU) and the USA are the biggest trading partner of all the South Asian countries, such preferential tariff arrangements could lead to significant erosion of preferences enjoyed currently by the South Asian Developing Countries such as, Bangladesh and Nepal. In this backdrop, the main objective of the present study is to investigate the potential economic impacts of tariff eliminations under TPP and TTIP on various macro and trade variables of Bangladesh and Nepal. In this context, a standard computable general equilibrium (CGE) analysis has been adopted by using the Global Trade Analysis Project (GTAP) model and database to explore the aggregate impact as well as sectoral implications. The analysis evinces that complete integration in terms of tariff elimination under these two mega deals, Bangladesh and Nepal could face tremendous negative impact on their economy. The analysis also suggests that Bangladesh and Nepal may consider joining to the TPP to minimize the negative economic impact due to the mentioned deals. JEL Classification Code: F14, F15, F17